PENGARUH MODEL PEMBELAJARAN KOOPERATIF DENGAN STRATEGI INDEX CARD MATCH TERHADAP HASIL BELAJAR BIOLOGI PADA POKOK BAHASAN DUNIA TUMBUHAN SISWA KELAS X SMA NEGERI 17 BATAM - Nurhaty Purnama Sari; Destaria Sudirman; Kalwini Kalwini (SIMBIOSA, 2014)
Research on the effects of cooperative learning with Index Card Match strategies on learning outcomes on the subject of biological plant word class X SMA Negeri 17 Batam school year 2012/3013. This study aims to prove the effect of cooperative learning with Index Card Match strategy to student learning outcomes. This study is was quasi experimental research with randomized Posttest Only Control Group Design. The population in this study was student at class X SMA Negeri 17 Batam, the sample in this which experimental class was X1 and X4 classes was a control class. Sampling was simple random sampling and the analysis data with t-test. Based on the analysis of the data showed that the experimental class had an average of 71,875 was higher than the control class 59,359. Price table = 2,00 while 5,228 t, so ttable tcount that the hypothesis is accepted. It could be concluded that the application of cooperative learning model to strategies Index Card Match had a significant effect on the results of biological studies on the subject of plants word class X SMA Negeri 17 Batam school year 2012/2013. Keyword: Cooperative Learning, Index Card Match, Learning Autcomes.